1992
DOI: 10.1002/mrd.1080320207
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of vascular cell behavior by transforming growth factors β

Abstract: The vascular cell responses to the type 1, 2, and 3 isoforms of transforming growth factor-beta (TGF-beta 1, TGF-beta 2, TGF-beta 3) were studied using bovine aortic endothelial (BAECs) and smooth muscle cells (BASMC3) as well as rat epididymal fat pad microvascular endothelia (RFCs). Three distinct bioassays indicated that TGF-beta elicits results that do not differ significantly from those of the TGF-beta 1 isoform in all three cell populations. These assays are: inhibition of proliferation, cell migration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 24 publications
3
39
2
Order By: Relevance
“…This suggests that TGFβ signalling may lead to mesenchymal differentiation, more specifically, smooth muscle differentiation, as α-SMA is a marker of myofibroblast formation. This is consistent with previous literature stating that TGFβ signalling may lead to the formation of pericytes and smooth muscle cells (13)(14)(15) …”
Section: Tgfβ Signalling Inhibits Endothelial Differentiation While Psupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that TGFβ signalling may lead to mesenchymal differentiation, more specifically, smooth muscle differentiation, as α-SMA is a marker of myofibroblast formation. This is consistent with previous literature stating that TGFβ signalling may lead to the formation of pericytes and smooth muscle cells (13)(14)(15) …”
Section: Tgfβ Signalling Inhibits Endothelial Differentiation While Psupporting
confidence: 93%
“…In vivo studies initially indicated that TGFβ signalling inhibits endothelial proliferation and migration while stimulating the differentiation of cells into mesenchymal phenotypes, more specifically to pericytes and smooth muscle cells. (13)(14)(15). However, stimulatory effects of TGFβ have also been reported on angiogenesis in vivo (1,(16)(17).…”
Section: Role Of Transforming Growth Factor Signalling In Marrow Stemmentioning
confidence: 99%
“…Angiogenesis is promoted by growth factors including vascular endothelial growth factor (VEGF) (Millauer et al, 1993;Ferrara et al, 1996), basic fibroblast growth factor (bFGF) (Klein et al, 1997), transforming growth factor beta 1 (TGF-β1) (Roberts et al, 1986;Madri et al, 1992), and the angiopoieteins (Sato et al, 1995;Maisonpierre et al, 1997). In addition to growth factors, the extracellular matrix (ECM) also plays an essential role in regulating angiogenesis and vascular remodeling (Stromblad and Cheresh, 1996;Eliceiri and Cheresh, 2001;Iivanainen et al, 2003;Stupack and Cheresh, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…ALK1/Smad1/5 activates cell proliferation and migration and is more related to the angiogenic state with the expression of inhibitor of DNA binding 1 (Id-1) and endoglin, among others (Byfield and Roberts, 2004;Goumans et al, 2003b;Goumans et al, 2002;Wu et al, 2006). TGF-␤ has been described to either activate or repress the process of angiogenesis (Madri et al, 1992;Roberts et al, 1986;Vinals and Pouyssegur, 2001;Yang and Moses, 1990). The existence of these receptors and their downstream responses may then reconcile contradictory TGF-␤-mediated effects observed in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%